2014 IEEE International Symposium on Information Theory 2014
DOI: 10.1109/isit.2014.6874789
|View full text |Cite
|
Sign up to set email alerts
|

Achievable secure degrees of freedom of MISO broadcast channel With alternating CSIT

Abstract: We study the problem of secure transmission over a two-user Gaussian multi-input single-output (MISO) broadcast channel under the assumption that the channel to each receiver is conveyed either perfectly (P) or with delay (D) to the transmitter. Denoting S 1 and S 2 to be the channel state information at the transmitter (CSIT) of user 1 and user 2, respectively; the overall CSIT can then alternate between four states, i.e., (S 1 , S 2 ) ∈ {P, D} 2 . We denote λ S 1 S 2 be the fraction of time the state S 1 S 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Proof: The proof of (85a)-(85f) follows along similar lines as in Lemma 1. In what follows, we now provide the proof of (85g).…”
Section: Appendix IV Proof Of Theoremmentioning
confidence: 83%
See 3 more Smart Citations
“…Proof: The proof of (85a)-(85f) follows along similar lines as in Lemma 1. In what follows, we now provide the proof of (85g).…”
Section: Appendix IV Proof Of Theoremmentioning
confidence: 83%
“…As opposed to the model in [26], the model that we study in this paper as shown in Figure 2 is more general, since it allows more leverage to the transmitter to choose between four possible states, i.e., PP, PD, DP, and DD. Specializing the results in this work to the model studied in [26] reveals that the encoding scheme in [26] outperforms the scheme that we developed in [1] (SDoF of 3/2 vs. 4/3). However, the outer bound that we have established in this work is more general; and, it subsumes the outer bound in [26] and the one developed in the context of broadcast channel with delayed CSIT in [21].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Only recently, the impact of imperfections on the DoF was investigated from various perspectives. Those include cases in which some channels are perfectly known, while others are completely unknown [9,10], cases in which the CSIT is available however only in a delayed or outdated fashion [11][12][13][14]. In other cases the knowledge of the channel is reduced to the channel coherence patterns [15] or the topology of the network [16,17].…”
Section: Introductionmentioning
confidence: 99%